Women in Political Power and School Closure during COVID Times - Natalia Danzer; Sebastian Garcia-Torres; Max F. Steinhardt; Luca Stella (Institute of Labor Economics (IZA), 2023)
This study explores the relationship between women's representation in political power and school closures during the COVID-19 pandemic. Using a cross-country dataset in Europe, we document a striking negative relationship between the share of female members in national governments and school closures. We show that a one standard deviation increase in female members of national governments is associated with a reduction in the likelihood of school lockdowns by 24% relative to the average share of school closures. This result is robust to an extensive set of sensitivity checks. We attribute this pattern to a higher awareness of female politicians about the potential costs that school closures imply for families.
Keywords: H52; I18; I20; J13; J16; 330; school closures; COVID-19; gender; political economy